Diseño de una máquina automatizada para la producción de empanadas (2017)
In this project was presented the design of a machine that performs the whole process of manufacturing a pie from the rolling of the dough to the shaping of the product, for this purpose Performed an analysis of the current situation of the process, then it was decided to define and evaluate three solution alternatives that are feasible and give solution to the proposed problem, the design of the machine was realized taking into account the loads it supports and performing the validation Of these values by means of finite element software.